Thank you / Nur Azimah Idris - Idris, Nur Azimah (Unit Penerbitan Dan Publisiti JSKM, 2022)
That night, fifteen years ago, Through one phone call, we received the news, The eldest’s weeping broke my heart and soul, It dawned on me that you will never come back, To Allah you return, with heavy heart we accept.